2020
DOI: 10.1111/acps.13254
|View full text |Cite
|
Sign up to set email alerts
|

Employment among people with schizophrenia or bipolar disorder: A population‐based study using nationwide registers

Abstract: Objective To assess the employment rate and the related background factors among people with schizophrenia or bipolar disorder. Methods We identified all people in Sweden aged 18–64 years diagnosed with schizophrenia or bipolar disorder in nationwide registers in the years 2006–2013. The identified individuals were grouped by main activity or source of income. The association between background factors and employment was analyzed with generalized estimating equations (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 37 publications
(59 reference statements)
8
38
0
Order By: Relevance
“…Additionally, the increased risk was observed in both sexes. Schizophrenia and psychoses as severe mental disorders have been associated with high rates of both unemployment and work disability ( Holm et al, 2021 ; Marwaha et al, 2007 ; Salkever et al, 2007 ). Targeted vocational interventions for them have been found effective in achieving higher work involvement ( Falkum et al, 2017 ; Tsang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the increased risk was observed in both sexes. Schizophrenia and psychoses as severe mental disorders have been associated with high rates of both unemployment and work disability ( Holm et al, 2021 ; Marwaha et al, 2007 ; Salkever et al, 2007 ). Targeted vocational interventions for them have been found effective in achieving higher work involvement ( Falkum et al, 2017 ; Tsang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of our participants, 34% had at least a tertiary education level compared to one local study in a less urbanized population that showed a much smaller tertiary education percentage (6%) ( 55 ). Our participants' education level is also higher when it is compared to those in a population-based study using nationwide registers, which occurred in one European country and in which only 12% had a tertiary educational level ( 56 ). Our patients' educational backgrounds are similar to those investigated in a study done at the same center on common medical illnesses, which revealed a slightly higher tertiary education level percentage (36%) ( 57 ).…”
Section: Discussionmentioning
confidence: 60%
“…(n = 187) rate of unemployment in this study, and has been associated with younger age and higher educational attainment 29,31,32 , as well as less severe SMI symptoms 29,32 . All of these might help people to acquire good digital skills and this may be directly linked with this study's finding that employed participants were more likely to have Foundation Skills compared to those not in employment.…”
Section: Discussionmentioning
confidence: 68%
“…This could be a sampling issue in our study and might not be representative of the total SMI population. However, it may also be explained by the fact that employment is less common in people with SMI, [28][29][30] , as shown by the 75.1%…”
Section: Discussionmentioning
confidence: 99%